Business Education Curriculum Content and Entrepreneurial Skills Development of Business Education Students in Public Universities in Lagos State, Nigeria - Elizabeth Remilekun Ore; Abosede Mariam Hassan (EduLine: Journal of Education and Learning Innovation, 2023)
This study examined the effectiveness of Business Education curriculum content and the entrepreneurial skills development of Business Education students in public universities in Lagos State, Nigeria. The study examined the extent to which Business Education curriculum content has helped to build students entrepreneurial skills. One hypothesis was formulated and tested at 0.05 level of significance. Descriptive survey research design method was adopted for the study. The population of the study was 100 to 400 level Business Education students from two public universities in Lagos State and purposive sampling technique was used to draw the sample size of 200 participants from the population. A four rating structured questionnaire titled “Effectiveness of Business Education Curriculum Content and Entrepreneurial Skills Development of Students’” (EBECESDS) was employed to gather data for the study. Regression statistics was used to test the hypothesis. Results from the findings revealed that Business Education curriculum content does not equip students with the required entrepreneurial skills needed to be self-reliant. Based on the findings, the study recommended that the curriculum content should be enriched and updated on a regular basis.